Expansion of T helper type 17 lymphocytes in patients with chronic granulomatous disease - Horváth, Radek; Rožková, D; Lašťovička, J; Poloučková, A; Sedláček, P; Šedivá, A; Špíšek, R (Clinical and experimental immunology, 2011)
Hyper-immunoglobulin (Ig)E syndrome (HIES) is a primary immunodeficiency associated with mutations in STAT3 resulting in impaired development of T helper type 17 (Th17) lymphocytes. HIES patients with a reduced frequency of Th17 cells present with infections caused by Staphylococcus aureus and/or Candida strains. The same spectrum of pathogens is present in patients with chronic granulomatous disease (CGD).We analysed the characteristics of the Th17 compartment in HIES and CGD. HIES patients showed very low numbers of Th17 cells. By contrast, the frequency of Th17 cells and production of Th17-derived cytokines was significantly higher among CGD patients when compared to both control samples and HIES. Naive CD4(+) cells in CGD patients had a normal capacity to differentiate into IL-17-producing cells and the numbers of Th17 cells in the CGD patients normalized following successful bone marrow transplantation. Our findings complement recent data on the importance of Th17 cells for elimination of infections with C. albicans and S. aureus.
Keywords: transplantace hematopoetických kmenových buněk; Transplantation, Homologous; Candidiasis; ELISA; Membrane Glycoproteins; lidé; ženské pohlaví; homologní transplantace; Granulomatous Disease, Chronic; buněčná diferenciace; buňky Th17; Job Syndrome; NADPH-oxidasy; Cell Differentiation; průtoková cytometrie; Th17 Cells; studie případů a kontrol; Case-Control Studies; Interferon-gamma; mutace; Enzyme-Linked Immunosorbent Assay; chronická granulomatózní nemoc; Female; mužské pohlaví; Staphylococcus aureus; NADPH Oxidases; STAT3 Transcription Factor; transkripční faktor STAT3; předškolní dítě; Jobův syndrom; Adult; Flow Cytometry; membránové glykoproteiny; stafylokokové infekce; Interleukin-17; Child; interferon gama; interleukin-17; kandidóza; Staphylococcal Infections; Mutation; Humans; Lymphocyte Count; dospělí; Male; Hematopoietic Stem Cell Transplantation; Candida albicans; Child, Preschool; dítě; počet lymfocytů